Perlindungan Anak dalam Pernikahan di Bawah Umur: Studi Komparatif Indonesia, Mesir, dan Fikih Kontemporer - ramadhania, safrida; safrida; Ahmad Izzudin; Ahmad antoni Hidayat (Institut Agama Islam Negeri Metro, 2025)
Abstract: The phenomenon of child marriage remains a serious issue in both Indonesia and Egypt due to its adverse impacts on children’s health, psychological well-being, and social development. This study aims to analyze child protection in early marriage through a comparative examination of Indonesian positive law, Egyptian family law, and contemporary fiqh perspectives. Using a normative-comparative method, the research examines legal and fiqh literature to identify common ground in child protection frameworks. The findings indicate that Indonesia has set a minimum marriage age of 19 through the revision of Marriage Law No. 16 of 2019, while Egypt establishes a minimum age of 18 under Law No. 126 of 2008. However, both countries face similar challenges: the effectiveness of regulations is weakened by the high number of marriage dispensation applications in Indonesia and by unregistered marriages (‘urfi) and strong cultural factors in Egypt. From a fiqh perspective, there is a shift from classical views emphasizing biological maturity (bulūgh) toward contemporary approaches that stress intellectual and psychological maturity (rushd) and the principles of maqāṣid al-sharī‘ah to prevent harm. This study concludes that effective child protection requires harmonization between stricter legal dispensation mechanisms and progressive contemporary fiqh values. Effective protection depends not only on formal regulation but also on strengthening public awareness to reject child marriage for the sake of broader social welfare. Keywords: child protection, child marriage, Indonesian law, Egyptian law, contemporary fiqh.